Durable disease regression with copanlisib treatment in PI3K-mutated metastasizing ameloblastoma: A case report - Meghan M Lynch; Pedro Hermida-Viveiros; Sean Stencel; Hannah Knott; Rusul Al-Maryati; Farres Obeidin; Borislav A Alexiev; Susan Abbinanti; Senthil Damodaran; Mark Agulnik; Seth M Pollack (Rare Tumors)
Ameloblastoma is a rare tumor arising from odontogenic cells that is benign, yet locally aggressive. Metastasizing ameloblastoma (METAM) is an ultra-rare ameloblastoma variant in which both primary and secondary tumors have histological features of benign ameloblastoma. This is a case report of a patient who presented with a jaw mass and subsequent lung metastases, later diagnosed as METAM. Initial treatments, including carboplatin, etoposide, and taxane-based chemotherapy, were ineffective. Molecular profiling revealed mutations including PIK3CA H1047R and BRAF V600E. The patient was enrolled in a tumor-agnostic trial and began treatment with copanlisib, a PI3K inhibitor, which resulted in a partial response and durable disease regression. After 76 cycles, she continues to tolerate therapy well with minimal adverse events. This case highlights the potential of targeted therapies such as copanlisib for treating METAM, providing a promising therapeutic option for patients with PIK3CA mutations.